2022
DOI: 10.3390/v14030515
|View full text |Cite
|
Sign up to set email alerts
|

Multiorgan and Vascular Tropism of SARS-CoV-2

Abstract: Although the respiratory tract is the main target of SARS-CoV-2, other tissues and organs are permissive to the infection. In this report, we investigated this wide-spectrum tropism by studying the SARS-CoV-2 genetic intra-host variability in multiple tissues. The virological and histological investigation of multiple specimens from a post-mortem COVID-19 patient was performed. SARS-CoV-2 genome was detected in several tissues, including the lower respiratory system, cardio-vascular biopsies, stomach, pancreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Here, we suggest the possibility of persistent viral shedding in the internal circulatory system. Although several postmortem studies of severe cases have been conducted ( 4 ), no studies have been conducted that investigate the persistence of SARS-CoV-2 particles in people who have recovered from non-severe COVID-19. Larger studies are needed to obtain sufficient information on the number of recovered patients who sustain internal viral shedding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we suggest the possibility of persistent viral shedding in the internal circulatory system. Although several postmortem studies of severe cases have been conducted ( 4 ), no studies have been conducted that investigate the persistence of SARS-CoV-2 particles in people who have recovered from non-severe COVID-19. Larger studies are needed to obtain sufficient information on the number of recovered patients who sustain internal viral shedding.…”
Section: Discussionmentioning
confidence: 99%
“…It may not be a misunderstanding that at least part of this ability may work in humans as well. Actually, post-mortem histological analyses revealed a wide spectrum of tropism of SARS-CoV-2 and its long-term existence in human organs ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is now ample evidence that SARS-CoV-2 infects diverse tissues throughout the body—far beyond the reach of a nasal swab—and that those infections can last long after obvious respiratory symptoms have cleared ( 9 11 ). A study by Stanford University researchers, for example, found that 4% of recovered COVID-19 patients were shedding viral RNA in their feces and reporting gastrointestinal (GI) symptoms 7 months after infection ( 12 ).…”
Section: Hidden Virusmentioning
confidence: 99%
“…Thus, due to the co-circulation of various SARS-CoV-2 strains within populations and in infected individual subjects, new variants with advantageous mutations and/or composite mutations can emerge. Subsequent new viral variants might carry new biological properties, such as viral escape from host-related immune response [ 6 ], specific human tissue or animal tropism [ 7 ], and possible modulations in SARS-CoV-2 properties in the environment through the Spike protein influencing viral behavior in samples, such as wastewaters [ 8 ].…”
Section: Introductionmentioning
confidence: 99%